Influence of molting and starvation on digestive enzyme activities and energy storage in Gammarus fossarum. - Laetitia Charron; Olivier Geffard; Arnaud Chaumot; Romain Coulaud; Ali Jaffal; Véronique Gaillet; Odile Dedourge-Geffard; Alain Geffard (PLoS ONE, 2014)
Among the many biological responses studied in ecotoxicology, energy-based biomarkers such as digestive enzyme activities and energy reserves appear to be useful predictive tools for detecting physiological disturbances in organisms. However, the use of these biological responses as biomarkers could be limited by the effects of confounding factors (biotic and abiotic) and physiological processes, such as the reproductive cycle. Thus, the optimal use of these biomarkers will be facilitated by understanding the effects of these factors on the energy metabolism of the sentinel species being studied. We considered abiotic factors (temperature and conductivity) in a previous study, whereas the present study investigated the effects of gender, the female reproductive stage, and food availability on the digestive enzyme activities and energy storage of Gammarus fossarum. The results indicated that, during the female reproductive cycle, the activities of digestive enzymes (amylase, cellulase, and trypsin) decreased significantly, whereas the levels of reserves (proteins, lipids, and sugar) increased until the last premolt stage. Restricted food diets only led to decreased amylase activities in both sexes. Food starvation also induced a decrease in the energy outcomes in females, whereas there were no effects in males. In general, the biochemical (digestive enzyme activities) and physiological (energy reserves) responses were more stable in males than in females. These results support the use of males fed ad libitum to limit the effects of confounding factors when using these energy biomarkers in Gammarus fossarum during biomonitoring programs.